EARTH SURFACE DEFORMATION OF THE SAKHALIN ISLAND FROM GPS DATA - A. S. Prytkov (Geodinamika i Tektonofizika, 2018)
The earth surface deformation was modeled for the North, Central and South Sakhalin on the basis of de‐ formation velocities recorded by the GPS stations of the Sakhalin Geodynamical Network. A pattern of contemporary horizontal deformation is intricate in the vicinity of the main submeridional faults of the island. On the island surface, the dominant deformation regime is compression; however, the spatial distribution of deformation is heterogeneous. The horizontal compression is mainly sublatitudinal and SW‐NE‐trending. In addition to compression, there are zones of rather intense right‐lateral strike‐slip in the northern and central parts of the island, while stretching dominates in the south‐eastern parts. The regional geodynamic setting is reflected in the seismicity of the island. Recently, the seismic activity has been increased in the areas characterized by intensive surface deformation, while the areas of low deformation rates correlate with the zones of weak and sparse seismicity.